Driving Access to Medicines With a Totality of Evidence Mindset: An Opportunity for Clinical Pharmacology. Issue 3 (28th November 2017) - Venkatakrishnan, Karthik; Cook, Jack
Abstract : Access to Medicine (AtM) initiatives have traditionally focused on enabling continuous availability and affordability of medicines for patients in the developing world. A more holistic view of AtM across the discovery–development–regulation–utilization continuum would also include participation in the development and timely access to emerging therapies in diverse populations in the era of precision therapeutics, built upon foundational clinical pharmacology principles, leveraging a Totality of Evidence (ToE) mindset.